2021
DOI: 10.33024/jkm.v7i4.4418
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Dark Chocolate Dan Wortel Dalam Menurunkan Intensitas Disminorea Primer

Abstract: Background: Dysminorrhea will get worse if accompanied by an unstable psychological condition. One of the causes of dysmenorrhea is hormonal factors where there is a hormonal imbalance. Pain during menstruation occurs due to high levels of prostaglandin hormones that make the uterine muscles contract. In Indonesia, the incidence of type dysmenorrhea primary is about 54.89% while the rest sufferers with secondary dysmenorrhea. Non-pharmacological therapy for dysmenorrhea is highly recommended, one of which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…This study similar to the results by Febriansyah (2020) on Midwifery Student Saleha Banda Aceh which showed a significant difference between giving dark chocolate before treatment (4.13) and after treatment (1.33) with a difference of 2.8 decreases. This study is also similar to the results of other studies which stated that giving 40 grams of dark chocolate per day was able to reduce the intensity of menstrual pain [14]. Therefore, in this study it can be concluded that 35 grams of dark chocolate can reduce the pain scale of dysmenorrhea in late adolescence.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This study similar to the results by Febriansyah (2020) on Midwifery Student Saleha Banda Aceh which showed a significant difference between giving dark chocolate before treatment (4.13) and after treatment (1.33) with a difference of 2.8 decreases. This study is also similar to the results of other studies which stated that giving 40 grams of dark chocolate per day was able to reduce the intensity of menstrual pain [14]. Therefore, in this study it can be concluded that 35 grams of dark chocolate can reduce the pain scale of dysmenorrhea in late adolescence.…”
Section: Resultssupporting
confidence: 91%
“…A research study found that the combination of cocoa with omega 3 fatty acids can inhibit inflammation and reduce cardiovascular risk factors in humans [13]. Another similar study also showed that the combination of dark chocolate with carrot boiled water produced a good antiinflammatory effect [14]. Taken together, the combination of dark chocolate with other herbal might increase the pharmacological effect, especially in antiinflamatory effect.…”
Section: Introductionmentioning
confidence: 95%